Analysis of Accountability Performance of Financial Management in Hasanuddin University as Legal Entity State University - Yohanis Sattu; Syamsu Alam; Mursalim Nohong (Magister Management, Hasanuddin University, 2020)
Accountability for the performance of financial statements has experienced rapid development. This study aims to analyze the level of influence of human resource competence and accounting systems on the accountability of financial management performance through the quality of financial reports. The quantitative approach is used to test and analyze the factors that affect the quality of financial reports and the accountability of financial management performance. Research sites at Hasanuddin University, Indonesia. The population and samples in this study were 85 financial employees in the financial sector at all Faculties and Work Units at Hasanuddin University with the status of ASN (State Civil Apparatus) as many as 85 people. Primary data collection techniques used a questionnaire (google form). The measurement scale used is a Likert scale with five components. The data analysis technique used path analysis. The results showed that the accounting system had a dominant effect on the quality of financial reports and the accountability of financial management performance compared to the human resource competency variables. Thus, the application of an accounting system can assist organizations in improving the quality of financial reports and accountability for financial management performance.